Growth and the Environment in Sudan: Myth or Reality of the EKC Hypothesis? - Sirag, Abdalla; Alnour, Mohammed; Gebrail, Mohammed (International Journal of Energy Economics and Policy, 2025)
The link between economic development and environmental outcomes has become increasingly evident. The study examines how economic growth influences environmental degradation in Sudan, using annual time series data spanning 1980-2022. The analysis accounts for potential structural breaks in unit root and cointegration testing. An Autoregressive Distributed Lag model is employed to assess the long-run relationship. The Environmental Kuznets Curve hypothesis is evaluated using three different approaches. Findings indicate that the EKC does not hold in the case of Sudan. The results suggest that, as developing a country, Sudan’s income level remains below the threshold at which economic growth would start to reduce environmental harm. The study also highlights the significant impact of energy consumption on the country’s carbon emissions. To address these challenges, robust and well-enforced environmental policies are recommended to mitigate the adverse effects of future generations.